Pengaruh Labelisasi Halal dan Kualitas Produk Terhadap Minat Pembelian Produk Makanan (Studi Kasus Di Desa Cilalawi Purwakarta) - Dila Nurfadilah; Asep Solihin; Wiwin Suhada (Fakultas Agama Islam Universitas Wiralodra, 2026)
This study aims to analyze the effect of halal labeling and product quality on consumer purchasing interest in food products in Cilalawi Village, Purwakarta. The method used is a quantitative approach with a survey technique through distributing questionnaires to 99 respondents, and analyzed using multiple linear regression. . The results show that halal labeling has no significant effect on purchasing interest with a significance value of 0.449 and a regression coefficient of 0.144. Conversely, product quality has a positive and significant effect on purchasing interest with a significance value of < 0.001 and a regression coefficient of 0.7717. Simultaneously, halal labeling and product quality have a significant effect on purchasing interest with an F value of 72.000 (p < 0.001) and a coefficient of determination (R²) value of 0.600. These results imply that improving product quality should be a top priority for MSME actors, while education value of 0.600. These results imply that improving product quality should be a top priority for MSME actors, while education the importance of halal labeling still needs to be improved among the community.